2021
DOI: 10.1002/smll.202005473
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall FeS2 Nanoparticles‐Decorated Carbon Spheres with Laser‐Mediated Ferrous Ion Release for Antibacterial Therapy

Abstract: Sulfur and its derivatives, including sulfur-containing inorganic and organic compounds, are known to possess broad-spectrum antibacterial properties and have been efficiently used in treating dermatological disorders and plant diseases. [2-4] However, the bulk quantities required for application and high hydrophobicity of sulfur have limited its use. [5] As such, the development of synthetic nanotechnology has provided an exciting new avenue for the use of sulfur. Recent studies have indicated that inorganic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…One hundred microliters of microorganisms (10 8 CFU mL −1 ) with different concentrations of 3-HB alkyl esters (2.5 mL) and MHB or SDB (2.5 mL) were cultured at 37 °C under shaking at 180 rpm. Antimicrobial kinetics was determined by OD 600nm using a spectro-photometer (HACH, USA) at 2, 4, 7, 10, 13, 16, 18, and 20 h. The bacteria incubated with PBS served as a negative control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One hundred microliters of microorganisms (10 8 CFU mL −1 ) with different concentrations of 3-HB alkyl esters (2.5 mL) and MHB or SDB (2.5 mL) were cultured at 37 °C under shaking at 180 rpm. Antimicrobial kinetics was determined by OD 600nm using a spectro-photometer (HACH, USA) at 2, 4, 7, 10, 13, 16, 18, and 20 h. The bacteria incubated with PBS served as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…1, 2 Microbial infections cause thousands of people to die every year because of antibiotics. 3 To solve this problem, researchers actively design and synthesize new antibacterial agents and material, 4,5 including antimicrobial peptides, 6 cationic polymers, 7 carbon-based nanomaterials, 8,9 and inorganic nanoparticles. 10,11 At present, organic antimicrobial agents are widely used in agriculture, medicine, food, and industries.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, numerous materials have been reported to inactivate microorganisms and viruses, such as metals [14][15][16] and organic materials [17][18][19][20] for virucidal applications, and molecules, [21][22][23][24][25] polymers, [26][27][28][29] and metals [30][31][32][33] for bactericidal applications. It was reported that metal nanoparticles, cationic polymers, or metal ions can interact strongly with negatively charged bacterial envelopes, providing them a highly efficient bactericidal capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with Ni 3 S 2 , the S 2p intensity of NiSFe-0.1 weakens due to the barrier of FeOOH nanosheets on the outer layer. Furthermore, the highresolution Fe 2p spectrum of the NiSFe-0.1 sample displays two pairs of spin-orbit coupling peaks together with one satellite peak: the lower binding energies at 706.6 eV and 719.72 eV are consistent with the FeÀ S bond, [23] and those at 711.8 eV and 725.1 eV are assigned to Fe 3 + . [24] The O 1s spectrum of NiSFe-0.1 (Figure 4d) includes metal-oxygen (530.35 eV), À OH (531.2 eV), and adsorbed H 2 O peaks (532.2 eV).…”
Section: Results and Discussmentioning
confidence: 93%